The effects of expectancies and patriotism on Chinese use intention of 5G network - Ke, Zhang; Jiayi, Hou; Long, Chen (Frontiers in Psychology, 2022)
China leads the world in the development and rollout of 5G network, yet little research has been done on the drivers of Chinese people’s adoption of 5G network, especially the specific role of national sentiments, such as the influence of patriotism on their attitude towards 5G network. The study obtained 804 effective online questionnaires from respondents of various ages, genders, areas, and educational levels. Results based a structural equation modeling analysis showed that patriotism was an antecedent to Chinese users’ cognition of the conditions provided by the government and telecom operators and the extent that users were influenced by media and surrounding people, which in turn increased users’ expectations of the performance of 5G network and their confidence in adapting to 5G network, and resulted in an increased willingness to use 5G network. This research helps to understand the role of patriotism, which is an emotional factor, in stimulating Chinese users’ attitudes towards 5G network at the time when 5G network is putting into large-scale commercial use in China.